#$&* course Mth 279 reminder to send some link that you said you would send last time but had a cpu malfunction.2/26 8 query 2
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): ------------------------------------------------ Self-critique rating: ********************************************* Question: 2. y ' + t y = 3 t YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: get each side to an appropriate integration solution dy(t) / dt = 3t - ty(t) ; simplify by taking t out on right side dy(t) / dt = t(3 - y(t) ) ; now divide by (3-y(t)) on both sides for integration [ dy(t) / dt / (3-y(t)) ] dt = t dt log (3-y(t)) = t^2/2 + c; simplify more 3-y(t) = e^(t^2/2 + c); now solve for y(t) to get y(t) = Ae^-(t^2/2) + 3
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): ------------------------------------------------ Self-critique rating: ********************************************* Question: 3. y ' - 4 y = sin(2 t) YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: working from example 1 basically in Chapter 2.3, I have widdled this one down a bit. let u = e^-4t and multiply each side. then by substituting d/dt(e^-4t) = -4y(t)e^-4t now this is the reverse product rule from which i had to look up. Now we can integrate this, in theory; int ( d/dt e^-4t y(t) )dt = int ( e^-4t sin2t ) dt ?? I had a lot of difficulty with this integration, later I found that it is actually a rule; which states; int exp(alpha t) sin ( beta t) dt = exp(alpha t)(-beta*cos(beta t)) + alpha*sin(beta t)) / alpha^2 + beta^2 I still could not sipher beta and alpha with e^-4t value. But my answer ended up to be y(t) = -1/10 (2sin(2t) + cos(2t))
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): ------------------------------------------------ Self-critique rating: ********************************************* Question: 4. y ' + y = e^t, y (0) = 2 YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: let u = e^t because p(t) = 1. and P(t) = t, so u will be e^t now multiply each by u to get; e^t dy(t)/dt + e^t y(t) = e^2t now apply the inverse product rule to the left side which states f(dg/dt) + g(df/dt) = d/dt(fg) this simplifies to d/dt e^t y(t) dt = e^2t dt the integration becomes e^t*y(t) = e^(t^2/2) + c simplified to solve for y(t) = e^(t^2/2) + ce^-t so with our initial condition y(0) = 2, our equation e^0 + ce^-(0) = 2 c = 3/2 now fill into our y(t) equation y(t) = e^t^2 / 2 + (3/2) e^-t confidence rating #$&*: ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): ------------------------------------------------ Self-critique rating: ********************************************* Question: 5. y ' + 3 y = 3 + 2 t + e^t, y(1) = e^2 YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: quite involved, going to brush over some typing p(t) = 3, so P(t) = 3t, which makes our u sub = e^3t multiply each by u, then you are left with the inverse product rule here to integrate more easily. when integrating, you get e^3t*y(t) = 2/3 t e^3t + 7/9 e^3t + 1/4 e^4t + c now solve for y(t) to after getting a common denominator to get y(t) = 24t + 28 + 9e^t + c*e^-3t solve for c to get that c = -52 - 8e^2 / e^3 fill back into the origional equation y(t) to get that y(t) = 24t + 28 + 9e^t + (-52 - 8e^2 / e^3)e^-3t i'm sure it can be simplified some.
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): ------------------------------------------------ Self-critique rating: ********************************************* Question: 6. The general solution to the equation y ' + p(t) y = g(t) is y = C e^(-t^2) + 1, t > 0. What are the functions p(t) and g(t)? YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: p(t) = -2t and g(t) = 0 I know this because looking at every other problem i've done, and each example, I always end up with my u sub in there, when my u sub is e^something, that something started out at an antiderivative of that before it was raised by e. g(t) = 0 therefore G(t) = 1 p(t) = -2t P(t) = -t^2 u = e^-t^2 confidence rating #$&*: ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary):